2011
DOI: 10.1007/s00296-010-1718-5
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes and cost-effectiveness of intraarticular injection of the rheumatoid knee

Abstract: Although intraarticular injections are important to the management of rheumatoid arthritis, there are few studies regarding the cost-effectiveness of alternative injection techniques. This randomized controlled study addressed the cost-effectiveness of two different low-cost, anatomic landmark palpation-directed intraarticular injection techniques. Ninety-six symptomatic rheumatoid knees were randomized to two different low-cost, palpation-guided intraarticular injection techniques utilizing (1) a conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Based on joint space volume, the 0.7‐mg dose (the lowest dosage used here) corresponds to 56‐mg TAA in a human knee joint, which is only 1.4 times higher the 40‐mg TAA bolus generally administered in patients. Even the 80 mg of bolus TAA administered in arthritic knees in several clinical studies did not result in adverse effects (C. E. Chavez‐Chiang et al, ; N. R. Chavez‐Chiang et al, ; Kumar, Dhir, Sharma, Sharma, & Singh, ; Popma et al, ). Moreover, the IA release of a dose of 60‐mg TAA from a PLGA MS platform, equivalent to the lowest dosage used in the current study, was shown to be safe in knee OA patients (Bodick et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Based on joint space volume, the 0.7‐mg dose (the lowest dosage used here) corresponds to 56‐mg TAA in a human knee joint, which is only 1.4 times higher the 40‐mg TAA bolus generally administered in patients. Even the 80 mg of bolus TAA administered in arthritic knees in several clinical studies did not result in adverse effects (C. E. Chavez‐Chiang et al, ; N. R. Chavez‐Chiang et al, ; Kumar, Dhir, Sharma, Sharma, & Singh, ; Popma et al, ). Moreover, the IA release of a dose of 60‐mg TAA from a PLGA MS platform, equivalent to the lowest dosage used in the current study, was shown to be safe in knee OA patients (Bodick et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Most studies evaluated injections into a single structure (42/49 (86%)),17 51 54 69 80 84–87 90–95 97–101 103–113 115–125 but seven studies (14%) investigated injections into more than one structure 52 71 88 89 96 102 114. In decreasing frequency, studies evaluated injections into bursae (19/49 (39%)),17 51 52 54 69 87 91–93 95 97 100 101 103 105 110 115 121 123 tendon sheaths (9/49 (18%)),71 89 102 106 108 111–113 116 tendons or fascia (8/49 {(16%)),96 102 107 112 119 120 124 125 perineural regions (6/49 (12%)),85 88 94 104 109 122 muscles (5/49 (10%)),86 97 114 117 118 cysts (2/49 (4%)),84 90 peritendinous regions (2/49 (4%)),71 102 wounds (1/49 (2%))52 and periarticular spaces (1/49 (2%)) 80…”
Section: Resultsmentioning
confidence: 99%
“…Three level 2 studies compared the efficacy of USG carpal tunnel injections to LMGIs 85 109 122. All three studies reported that USG carpal tunnel injections were less painful and more efficacious than LMGIs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature is limited, there is some evidence suggesting that guided procedures are a more cost effective treatment strategy. Researchers evaluated ultrasound versus blind injections in patients with inflammatory and non-inflammatory arthritis and found a reduction of $7-17 per patient per year with the use of ultrasound and even bigger reduction in costs of $64-224 per patient per year in a subgroup identified as ''responders'' [17][18][19].…”
Section: Indications and Specifications For Ultrasound Guided Proceduresmentioning
confidence: 99%